Vocabulary learning through vocabulary scrapbook - Md. Deni, Ann Rosnida; Zainal, Zainor Izat; Mohamed, Mazlin (Faculty of Communication and Modern Languages, Universiti Utara Malaysia, 2007)
For the last 25 years, the field of English language teaching has witnessed significant responses to the incorporation of vocabulary learning in the language classroom. Vocabulary learning has been viewed as central to language learning and being of critical importance to the typical language learner. According to Coady (1997), there is a general agreement among vocabulary learning advocators that the heart of communicative competence is lexical knowledge. Such shift in emphasis in the field of ELT, followed by continuous research on vocabulary learning, have shed light on, and have provided valuable information about what to do and what to focus on. All these imply that the teachers in the language classrooms can utilise many interesting and creative techniques in vocabulary teaching and learning. A project called Vocabulary Scrapbook was introduced to the first semester students at Universiti Kuala Lumpur, Malaysia France Institute with the aim to enrich students’ vocabulary inventories via specific vocabulary learning strategies. This paper describes how the principles underlying vocabulary learning are put into practice in the project, the problems faced by the teachers and students in carrying out the project, and the effectiveness of the project in improving students’ inventories of words and phrases. A survey carried out after the project was completed revealed the students’ positive reception of the project – viewing it as a useful tool in learning and enriching their vocabulary.